KEBISINGAN LALU LINTAS KENDARAAN BERMOTOR PADA RUAS JALAN DI KECAMATAN BANJARMASIN UTARA - Ihwati Nur Cahyani; Sidharta Adyatma; Deasy Arisanty (JPG (Jurnal Pendidikan Geografi), 2015)
The title of this research is “terrible noisy of traffic for public vehicle on side way at Kecamatan Banjarmasin Utara”. The aim of this research is to knowing degree for volume of public vehicle, intensity of scale improvement terrible noisy (dB A) and connection between totality of public vehicle and also degree of terrible noisy (dB A) on side way of artery primer and also secondary at Kecamatan Banjarmasin Utara on the busily times it is at 07.00-08.30 WITA, 12.30-14.30 WITA and also at 16.00-18.00 WITA.The population for this research is all of public vehicle whiches riding on side way at Kecamatan Banjarmasin Utara. The act of this research on every side way at Kecamatan Banjarmasin Utara on monday, friday, saturday and also sunday with interval’s time regulation by KEP-48/MENLH/11/1996 which timing that doing during activity. Technicaly of accumulation data in this research by using observation method and study of document. The analysis for this research by using statistic descriptive that also used percentage  formula, interval of class and corelation one predictor to knowing connection between totality of public vehicle and also degree of terrible noisy (dB A) on side way of artery primer and also secondary at Kecamatan Banjarmasin Utara.The results of this research is percentage of public vehicle on artery primer side way and secondary too at busily times that is a lot, a little bit and a lot, intencity scale of terrible noisy within this research is so loudly that is around 80 (dB A) until 100 (dB A) and also there has connection between percentage of public vehicle with percentage terrible noisy on the side of way Sultan Adam and also Brigjen H Hasan Basri at Kecamatan Banjarmasin Utara at busily times. Key Word : Terrible noisy, of traffi,c for public vehicle